2014
DOI: 10.5507/ag.2014.006
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics affecting sport tourism choices: A structural model

Abstract: Background: Effective tourism management in the field of sports tourism requires an understanding of differences in socioeconomic characteristics both within and between different market segments. Objective: In the broad tourism market demographic characteristics have been extensively analyzed for differences in destination choices, however little is known about demographic factors affecting sport tourists' decisions. Methods: A sample of Slovenian sports tourists was analyzed using data from a comprehensive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
(35 reference statements)
0
9
0
1
Order By: Relevance
“…Previous studies on visitor experiences in theme parks indicate that, following two‐dimensional matrix IPA model (Martilla & James, ) and SERVQUAL instrument (Zeithaml, Berry, & Parasuraman, ) which attempted to set five variables for evaluating a service (i.e., tangibility, reliability, assurance, responsiveness, and empathy), many other scholars kept on developing refined tools and adding new variables in order to measure and evaluate a service quality in a more comprehensive approach in the theme park industry (Brown, Churchill Jr, & Peter, ; Oh, ; Slak Valek, Shaw, & Bednarik, ; Van Ree, ) while other researchers attempted to investigate customer's satisfaction from the perspective of safety, security, and environment uniqueness (Pikkemaat & Schuckert, ). Similarly, Tsang et al () notified that assurance, empathy, and responsiveness are key factors to predict the theme park visitors' satisfaction levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on visitor experiences in theme parks indicate that, following two‐dimensional matrix IPA model (Martilla & James, ) and SERVQUAL instrument (Zeithaml, Berry, & Parasuraman, ) which attempted to set five variables for evaluating a service (i.e., tangibility, reliability, assurance, responsiveness, and empathy), many other scholars kept on developing refined tools and adding new variables in order to measure and evaluate a service quality in a more comprehensive approach in the theme park industry (Brown, Churchill Jr, & Peter, ; Oh, ; Slak Valek, Shaw, & Bednarik, ; Van Ree, ) while other researchers attempted to investigate customer's satisfaction from the perspective of safety, security, and environment uniqueness (Pikkemaat & Schuckert, ). Similarly, Tsang et al () notified that assurance, empathy, and responsiveness are key factors to predict the theme park visitors' satisfaction levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sport participation and consumption motives should be examined as a multidimensional construct, comprising multiple psychosociological factors including motivation and satisfaction issues as well as demographic factors (Hungenberg et al, 2016; Rohm et al, 2006). Hence, sociodemographic characteristics were important for defining clusters in sport tourism (Finn, 2012; Slak Valek et al, 2014). The study found certain differences across active sport clusters in terms of sociodemographic characteristics of three identified clusters.…”
Section: Results and Findingsmentioning
confidence: 99%
“…Group identity was deeply explored aiming to differ each group from other consumer segments, and consequently, many different motivational scales were argued in the literature (Hodeck & Hovemann, 2016;Hungenberg et al, 2016;Kim & Ritchie, 2012;Slak Valek et al, 2014). Recent studies suggested using specially designed Sport and Tourism Motivational Scale to explain the main reasons for active sport tourism consumption and to indicate unique market segments.…”
Section: Motivation In Sports and Recreationmentioning
confidence: 99%
See 1 more Smart Citation
“…La investigación realizada ha tenido como objetivo conocer la opinión de los usuarios de centros deportivos sobre qué aspectos consideran importantes y cuáles de ellos les motivan para inscribirse en uno de dichos centros deportivos, diferenciando las opiniones en función de las diferentes características sociodemográficas: género, nivel de estudios, ocupación y nivel socioeconómico. El estudio de las variables sociodemográficas como elementos a tener en cuenta para entender los fenómenos de comportamiento del consumidor, es algo ya habitual en la literatura científica, lógicamente también en el contexto deportivo, donde encontramos ejemplos que se han basado en ese tipo de análisis para analizar, por ejemplo, la imagen de marca en servicios deportivos (Alguacil, Crespo-Hervás & Pérez-Campos, 2020) la segmentación en servicios fitness (Valcarce & Díez, 2017) o las preferencias de los consumidores en relación al turismo deportivo (Slak-Valek, Shaw & Bednarik, 2014). Este tipo de análisis permite la segmentación de los consumidores (Nuviala et al, 2014), conociendo los distintos perfiles de usuario y favoreciendo un mejor y más detallado entendimiento de los procesos.…”
Section: Discussionunclassified